Writing Resistance in the Second World War - L. Chapman, Jane. author. aut Link
XVI, 218 p.
Keywords: This book aims to extend existing historical, literary and media knowledge of neglected written voices as a form of print participation in the Second World War. Uniquely, it is framed by an awareness of contemporary requirements for both secrecy and deception, which, it is argued, were nevertheless characterised by a rare participatory inclusivity in terms of writers and audiences - that has hitherto only been perceived as a characteristic of ‘citizen’s journalism’ in the internet age. Comparative cases of resistance using newspapers during the Second World War comprise original and clandestine sources from France, Belgium, the Netherlands, Norway, and Britain - analysed for the effect that intelligence and planned deception had on local publications as well as on readers of resistance broadsheets. Jane L. Chapman is Professor Emeritus of Media History at the University of Lincoln, UK.